2020
DOI: 10.3390/healthcare8030244
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an Integrated Healthcare Program for Korean Rural Older Adults: A Quasi-Experimental Study

Abstract: Studies have been conducted on the development of healthcare programs for older adults in rural areas, not only in Asia but also in Europe and the United States. However, these reports have been limited by largely non-comprehensive results, lack of demand surveys, or programs with no systematic development. The purpose of this study was to develop an integrated healthcare program for rural older adults and investigate the effects of the program. A nonequivalent control group pretest–posttest design was used. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Understanding how these experiences affect frail older adults' daily lives can inform providers and policy makers about the content and quality of healthcare services they need. Research has shown that providing integrated, holistic healthcare-including addressing age-related conditions-improves older adults' physical functions, loneliness, and self-efficacy roles (Kim et al, 2020). Considering older adults' in-depth perspectives is crucial when designing optimal healthcare services.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding how these experiences affect frail older adults' daily lives can inform providers and policy makers about the content and quality of healthcare services they need. Research has shown that providing integrated, holistic healthcare-including addressing age-related conditions-improves older adults' physical functions, loneliness, and self-efficacy roles (Kim et al, 2020). Considering older adults' in-depth perspectives is crucial when designing optimal healthcare services.…”
Section: Discussionmentioning
confidence: 99%
“…The RAM is a conceptual framework that assesses the adaptation level of an individual or group, which is a result of the coping strategies employed to manage internal or external stimuli. It has been widely utilized as a theoretical framework in studies examining the effects of interventions for people with chronic health conditions [54,55]. The RAM views human beings as adaptive systems that strive to achieve a state of adaptation, which entails living in integration with their surrounding environment.…”
Section: Data Extraction and Synthesismentioning
confidence: 99%